2021
DOI: 10.1097/scs.0000000000008306
|View full text |Cite
|
Sign up to set email alerts
|

Does the Geographical Distribution of Facial Trauma Surgeons Correspond to Facial Trauma Burden? A Nationwide Population-Level Analysis

Abstract: It is unknown if craniofacial trauma services are inequitably distributed throughout the US. The authors aimed to describe the geographical distribution of craniofacial trauma, surgeons, and training positions nationwide. State-level data were obtained on craniofacial trauma admissions, surgeons, training positions, population, and income for 2016 to 2017. Normalized densities (per million population [PMP]) were ascertained. State/ regional-level densities were compared between highest/lowest. Risk-adjusted ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several large database studies have found that there was a greater incidence of orbital fractures in the south compared to other geographic regions but no significant difference in the rates of operation 1,24 . There were also regional differences in the density of facial trauma surgeons with fewer facial trauma surgeons in the south compared to the west by population density 25 . This can impact the timely receipt of postoperative care with more reliance on ER visits rather than office visits to address symptoms in locations with fewer surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large database studies have found that there was a greater incidence of orbital fractures in the south compared to other geographic regions but no significant difference in the rates of operation 1,24 . There were also regional differences in the density of facial trauma surgeons with fewer facial trauma surgeons in the south compared to the west by population density 25 . This can impact the timely receipt of postoperative care with more reliance on ER visits rather than office visits to address symptoms in locations with fewer surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 There were also regional differences in the density of facial trauma surgeons with fewer facial trauma surgeons in the south compared to the west by population density. 25 This can impact the timely receipt of postoperative care with more reliance on ER visits rather than office visits to address symptoms in locations with fewer surgeons. A multitude of other factors, including the severity of the injury, patterns of facial fracture, and public safety laws may contribute to these regional differences and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%